2017
DOI: 10.1080/1472586x.2017.1362959
|View full text |Cite
|
Sign up to set email alerts
|

Digital photographic practices as expressions of personhood and identity: variations across school leavers and recent retirees

Abstract: Over the last two decades, digital photography has been adopted by young and old. Many young adults easily take photos, share them across multiple social networks using smartphones, and create digital identities for themselves consciously and unconsciously. Is the same true for older adults? As part of a larger mixed-methods study of online life in the UK, we considered digital photographic practices at two life transitions: leaving secondary school and retiring from work. In this paper, we report on a complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…These results indicate a transition from an affective toward an increasingly cognitive knowledge-based sense of aesthetics, and generally provide evidence for the fundamental importance of emotional processing. Another aspect of aging has been addressed by Orzech et al (2017) who distinguished between a more “inwards oriented perspective” of young adults in contrast to a more outward oriented use of images by older people, representing differences in digital social norms of co-creation of self, as well as a priority for privacy for others. The relations to self-image was also stressed by Pelowski et al (2017) as an important feature to understand aesthetic responses.…”
Section: The Usermentioning
confidence: 99%
“…These results indicate a transition from an affective toward an increasingly cognitive knowledge-based sense of aesthetics, and generally provide evidence for the fundamental importance of emotional processing. Another aspect of aging has been addressed by Orzech et al (2017) who distinguished between a more “inwards oriented perspective” of young adults in contrast to a more outward oriented use of images by older people, representing differences in digital social norms of co-creation of self, as well as a priority for privacy for others. The relations to self-image was also stressed by Pelowski et al (2017) as an important feature to understand aesthetic responses.…”
Section: The Usermentioning
confidence: 99%
“…The theory of networked individualism explains the change from traditional social groups to digitally connected individuals and the increasing importance of these personal networks (Rainie & Wellman, 2012 as cited in Orzech, Moncur, Durrant, James & Collomosse, 2017). Social networks have been investigated intensely and shape the way we live and see ourselves: "To know who we are, we must understand how we are connected" (Christakis & Fowler, 2009, p. xiii).…”
Section: The Role Of Network In Identity and Personhoodmentioning
confidence: 99%
“…Research data visualisation helps educators/researchers explain complicated findings and improve how audiences remember what the research was all about. In order to achieve this, educators may need to be trained in identity management so that they can share their stories, experiences and opinions online (Lehmuskallio & Gómez-Cruz, 2016), especially as educational institutions regard images, logos, and videos as forms of symbolic leadership (Orzech et al 2017).…”
Section: Identity Management Competencesmentioning
confidence: 99%
“…These studies found that age, extraversion, self-control and self-efficacy influenced the amount and type of information disclosed on social media. Those who were younger, more extravert, had lower self-control and greater self-efficacy in their use and manipulation of social media were more likely to engage in disclosure information on social media (Krämer and Winter 2008;Orzech, Moncur, Durrant, James and Collomosse 2017;Yu 2014). Consequently, the motivations underlying social media use, as well as individual characteristics such as age, personality and psychological attributes, could influence the amount and type of self-disclosure that people engaged in on social media.…”
Section: Need For Relationships and Self-expressionmentioning
confidence: 99%